Evaluating virtual reality anatomy training for novice anesthesiologists in performing ultrasound-guided brachial plexus blocks: a pilot study - Xiaoyu Li; Siqi Ye; Qing Shen; Enci Liu; Xiujun An; Jinling Qin; Yang Liu; Xiuzhong Xing; Junping Chen; Bo Lu (BMC Anesthesiology)
Abstract Background Developing proficiency in ultrasound-guided nerve block (UGNB) demands an intricate understanding of cross-sectional anatomy as well as spatial reasoning, which is a big challenge for beginners. The aim of this pilot study was to evaluate the feasibility of virtual reality (VR)-facilitated anatomy education in the first performance of ultrasound-guided interscalene brachial plexus blockade among novice anesthesiologists. We carried out pilot testing of this hypothesis using a prospective, single blind, randomized controlled trial. Methods Twenty-one anesthesia trainees with no prior ultrasonography or nerve block training were included in this study. All participants underwent a training program encompassing theory and hands-on practice. Trainees were randomized into one of two groups: one received VR-assisted anatomy course while the other did not. Subsequently, both groups completed identical practical modules on ultrasound scanning and needle insertion. The primary end point was defined as the evaluation of trainees’ performance during their initial ultrasound-guided interscalene brachial plexus block, assessed using both the Global Rating Scale (GRS) and a task-specific Checklist. The secondary end point included the improvement in scores for written multiple-choice questions (MCQs). Results In evaluating practical ultrasound-guided nerve block skills, the VR group significantly outperformed the control group on the task-specific Checklist (29.23 ± 3.91 vs. 24.85 ± 5.13; P < 0.05), while both groups showed comparable performance on the GRS. Additionally, post-theoretical course MCQ scores increased substantially, with post-test results significantly surpassing pre-test scores in both groups (P < 0.001). However, intergroup analysis indicated no significant difference in score improvements between the VR and control groups (21.82 ± 12.30 vs. 18.33 ± 9.68, P > 0.05). Conclusions Overall, the findings of this pilot study suggest that immersive virtual reality training in anatomy may contribute to improving the proficiency of ultrasound-guided brachial plexus blocks among novice anesthesiologists. Incorporating VR into future anesthesia technique training programs should be considered. Trial registration ClinicalTrials.gov identifier: ChiCTR2300067437. Date of Registration Jan 9, 2023.